A novel electrochemical quercetin sensor based on Pd/MoS2-ionic liquid functionalized ordered mesoporous carbon. (1st September 2017) - Xu, Bingjie; Yang, Lite; Zhao, Faqiong; Zeng, Baizhao
Graphical abstract: A 3D Pd/MoS2 -IL-OMC nanocomposite is prepared and used for the electrochemical detection of QR; it presents good performance. Highlights: IL-OMC was used as support to improve the conductivity of MoS2. 3D Pd/MoS2-IL-OMC composite was employed for constructing quercetin sensor. The sensor showed high sensitivity and stability in sensing quercetin. Abstract: A quercetin (QR) sensor based on Pd/MoS2 -ionic liquid functionalized ordered mesoporous carbon (Pd/MoS2 -IL-OMC) composite is developed. The Pd/MoS2 -IL-OMC composite is prepared by using IL as anchor and OMC as substrate. MoS2 nanosheets are in situ grown on IL-OMC surface and then Pd nanoparticles are prepared on MoS2 nanosheets via chemical reduction method. As the nanocomposite combines the high conductivity of IL-OMC and the electrocatalytic activity of Pd nanoparticles and MoS2, the resulting sensor exhibits good performance towards QR, better than MoS2 -IL-OMC and Pd/IL-OMC nanocomposites modified electrodes. The electrochemical sensor allows for the selective determination of QR, with a detection limit of 8.0 nM (S/N = 3), a linear range of 0.020 μM–10 μM, and a sensitivity of 150.1 μA μM −1  cm −2 . It also shows good reproducibility and stability, and can be applied to the detection of QR in real samples.